PEMERIKSAAN LAJU ENDAP DARAH (LED) SEBAGAI INDIKATOR TERHADAP ABNORMALITAS ORGAN HATI KAMBING LOKAL - Jois M. Jacob; Yanse Y. Rumlaklak (Partner, 2010)
This study aims to determine th relationship between changes in blood erythrocyte sedimentation rate of liver abnormalities in local goats. Abnormal liver classified in bleeding (hemorrhagic), thickening of the bile ducts (cholestatic), the formation of connective tissue (fibrosis) and swelling (hepatomegaly). Abnormal scoring from 0 (normal) to 5 (liver damage above 75%). Erythrocyte sedimentation rate blood test done at the Laboratory of Clinical Pathology, Veterinary Faculty, University of Udayana. These results illustrate the influence of liver abnormalities of ESR values were analyzed with Spearman correlation coefficients according to Stell and Torrie (1991). Results showed 97% of local goats have the ESR value from 3 to 10 mm/24 hours with the type of liver damage such as bleeding 63%; swelling 44%; the formation of connective tissue 93% and 14% thickening of the bile duct.The results show that the value of the ESR is influenced by the presence of connective tissue formation (fibrosis), bleeding (hemorrhagic), and swelling (hepatomegaly) (P <0.05). It concluded that liver abnormalities in local goats, such as connective tissue formation (fibrosis), bleeding (hemorrhagic), and swelling (hepatomegaly) is correlated with the ESR so that the ESRs can be used as an indicator of liver abnormalities.Keywords : ESR, Hemorrhagic, Cholestatic, Fibrosis, Hepatomegaly